EFEKTIVITAS DESIGN LISDAS (LISTRIK CERDAS) MATERI RANGKAIAN LISTRIK BERBASIS WEB MELALUI PROJECT BASED LEARNING DALAM MENINGKATKAN KEMAMPUAN BERFIKIR KRITIS SISWA KELAS VI UPT SDN 02 TANJUNGSARI KOTA BLITAR - Aswitama, Lana Diyani; Fatih , Mohamad; Alfi, Cindya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Science that studies the universe and its contents, as well as the events that occur in it is known as natural science or science. It is created by specialists using scientific methods. One of the most important subjects in education is Natural Sciences (IPA). However, in reality, science education is still not liked by children because it is considered difficult and boring. Thus, using 30 research subjects, researchers conducted research at SD Negeri 02 Tanjungsari, Blitar City. By using lisdas (smart electricity) design media, the researcher used a purposive sampling strategy with group A (15 students) as the experimental class and group B (15 students) as the control class. Based on the research results, the pretest value for the experimental class was 0.1492 and the posttest value was 0.02548. The growth of critical thinking patterns in the experimental class is classified as "high" based on the score above. The posttest score for the experimental class was 1.053, while the pretest score for the control class was 833. This difference was caused by the experimental class's higher critical thinking patterns, so that the posttest for the experimental class was classified as "low". The class teacher questionnaire form received a response rate of 72%. This shows that testing media suitability is very useful. Thus, it can be said that students' critical thinking skills are improved effectively by using Lisdas media, namely web-based electrical circuit content obtained through project-based learning.